Pathological findings in a mouse model of Japanese encephalitis infected via the footpad - Fu, T.L.; Ong, K.C.; Wong, K.T. (2015)
We have developed and characterised a mouse model of Japanese encephalitis virus (JEV) infection via footpad inoculation in order to better mimic viral transmission by mosquito bites. Two-week-old and 5-week-old mice consistently developed signs of infection such as ruffled fur, weight loss, hunchback posture, tremors, mask-like facies and occasionally, hindlimb paralysis at 4 days post infection (dpi) and 11-13 dpi, respectively. Most of the animals died within 24 to 48 hours following the onset of signs of infection, with mortalities of 100% and 33.3% in 2-week-old and 5-week-old mice, respectively. Mild meningitis and variable parenchymal inflammation with formation of microglial nodules, focal necrosis and neuronophagia, and perivascular cuffing by inflammatory cells were observed in the caudate nucleus, putamen, thalamus, cerebral cortex, brainstem, and spinal cord. Viral antigens/RNA were demonstrated by immunohistochemisty and in situ hybridization, respectively, in most of these areas as well as in the hippocampus and cerebellum, albeit more focally. The pathological findings in this mouse model were generally similar to human Japanese encephalitis (JE) and other established JE models but perhaps, compared to other JEV mouse models, it demonstrates lethal encephalitic infection more consistently. We believe that our mouse model should be useful to study the pathogenesis of JE, and for testing anti-viral drugs and vaccines